Respon Nasabah Terhadap Product Positioning Tabungan Bank KALBAR - Listiana, Erna (Jurnal Administrasi Bisnis, 2011)
Competition in saving account product is a great effect on the number of customer.A greater product values offered then a greater number of customers who are usingthe services. Since positioning strategy describe a superior value, the positioning be-comes an important determining aspect for a customer in deciding to use the services.This study has an objectvie to evaluate customer perception on product positioningof saving account in Bank KALBAR. Survey was conducted to 50 respondent ofTASERNA saving account and 50 respondent in SIMPEDA saving account. Theresult showed that the SIMPEDA saving account is positioned as a saving accountwith a good attribute, such as an appropriate administration fee and service qual-ity. Meanwhile, the TASERNA saving account has a fair enough position in termof provisionâs simplicity, administration fee, interest rate, prizes offered, withdrawallimitation, physical saving book, and ATM facility.Keywords: product value, positioning, positioning strategy